Associations of Nutritional and Social Exposures in Utero, Early, and Later Childhood with Cognitive, Motor, and Social-Emotional Development in Indonesia (OR10-03-19) - Prado, Elizabeth (Curr Dev Nutr, 2019)
OBJECTIVES: To determine the association of biomedical and socio-environmental risk factors during pregnancy, early, and later childhood with cognitive (IQ), motor, social-emotional (SE), and executive function (EF) at age 3.5 and 9–12 y in Indonesia. METHODS: Children born to pregnant women enrolled in the Supplementation with Multiple Micronutrients Intervention Trial (SUMMIT) in 2001–2004 participated in follow-up studies at age 3.5 y in 2006 and 9–12 y in 2013. We assessed 359 children at both time points for outcomes of IQ, motor, SE and EF. We also assessed predictors of outcomes including biomedical risks (small for gestational age at birth: SGA; height-for-age z-score: HAZ; and child hemoglobin: Hb) and socio-environmental risks (HOME Inventory; maternal depression: MD). We calculated the residuals of earlier risks predicting the later scores, e.g., the residual of SGA at birth predicting HAZ at 3.5 y (rHAZ1), representing the deviation of HAZ at 3.5 y from the child's expected HAZ based on SGA. In Model 1, we entered SGA, representing in utero exposures. In Model 2, we added indicators at 3.5 y (rHAZ1, Hb, HOME, MD). In Model 3, we added indicators at 9–12 y (rHAZ2, rHb, rHOME, rMD) and the corresponding 3.5 y IQ, motor, SE, or EF scores. RESULTS: The coefficients for outcomes at early and later time points (Figure 1) show that SGA was not associated with any scores. Early (3.5 y) childhood rHAZ1 was associated with early IQ, motor, and EF, but was not independently associated with later (9–12 y) IQ, motor, or EF. Later childhood rHAZ2 was not associated with any scores. Early childhood HOME was independently associated with both early and later IQ, motor, and EF, while later childhood rHOME was not associated with any scores. Early Hb was not associated with any scores and later rHb was associated with motor scores only. MD during early childhood and rMD during later childhood were independently associated with later childhood SE. CONCLUSIONS: These findings support the importance of early and continual intervention throughout childhood to support healthy growth and even more importantly maternal mental health and nurturing home environments. This is essential for longer-term IQ, motor, SE, and EF. FUNDING SOURCES: Grand Challenges Canada, Allen & Turner Foundations, UNICEF, Centre for Health and Human Development, USAID-Indonesia, USDA NIFA #CA-D-NTR-2493-H. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: